(untitled) (Journal of Health, Population and Nutrition, 2011)
An observational study was conducted in the four southernmost provinces of Thailand aiming at determining the effect of international or Asian criteria-based body mass index (BMI) in predicting maternal anaemia, low birthweight (LBW), and preterm births among pregnant Thai women and the change in haemoglobin (Hb) level during pregnancy. Maternal anaemia was defined as a haemoglobin (Hb) level of <11 g/dL. Anaemia was detected in 27.4% and 26.9% of 1,192 pregnant women at their first prenatal visit and the third trimester respectively. The proportions of overweight and obese women according to the Asian criteria-based pre-pregnancy BMI were higher than the international criteria-based BMI (22.4% and 10.1% vs 15.5% and 3.4% respectively). No significant difference between pre-pregnancy BMI and pregnancy BMI at the first prenatal visit was demonstrated (mean±standard deviation=21.8±4.0 vs 22.8±4.1). Underweight women had a significantly higher prevalence of maternal anaemia, LBW, and preterm birth compared to women with normal weight. Overweight and obese women at pre-pregnancy by the Asian criteria-based BMI had a lower prevalence of anaemia. The Hb levels did not change significantly over time. In addition to BMI, maternal age, parity, and late prenatal visit were independently associated with maternal anaemia, low birthweight, and preterm birth. Underweight pregnant women classified by international or Asian criteria-based BMI increased the risk of maternal anaemia, low birthweight, and preterm birth. Key words: Anaemia; Body mass index; Observational studies; Pregnancy; Thailand DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7869 J HEALTH POPUL NUTR 2011 Jun;29(3):218-228